Promoting evidence informed policy making in Nigeria: a review of the maternal, newborn and child health policy development process - Chigozie Jesse Uneke; Issiaka Sombie; Namoudou Keita; Virgil Lokossou; Ermel Johnson; Pierre Ongolo-Zogo; Henry Chukwuemeka Uro-Chukwu (Tabriz University of Medical Sciences, 2017)
Background: There is increasing recognition worldwide that health policymaking process should be informed by best available evidence. The purpose of this study was to review the policy documents on maternal, newborn and child health (MNCH) in Nigeria to assess the extent evidence informed policymaking mechanism was employed in the policy formulation process. Methods: A comprehensive literature search of websites of the Federal Ministry of Health(FMOH) Nigeria and other related ministries and agencies for relevant health policy documents related to MNCH from year 2000 to 2015 was undertaken. The following terms were used interchangeably for the literature search: maternal, child, newborn, health, policy, strategy,framework, guidelines, Nigeria. Results: Of the 108 policy documents found, 19 (17.6%) of them fulfilled the study inclusion criteria. The policy documents focused on the major aspects of maternal health improvements in Nigeria such as reproductive health, anti-malaria treatment, development of adolescent and young people health, mid wives service scheme, prevention of mother to child transmission of HIV and family planning. All the policy documents indicated that a consultative process of collection of input involving multiple stakeholders was employed, but there was no rigorous scientific process of assessing, adapting, synthesizing and application of scientific evidence reported in the policy development process. Conclusion: It is recommended that future health policy development process on MNCH should follow evidence informed policy making process and clearly document the process of incorporating evidence in the policy development.